Effect of Deferiprone on Hepatic Expression of Hamp, Ftl, and Tfr1 Genes in an Iron-Overloaded Rat (Rattus norvegicus) Model - Salsabila, Nadhila Hasna; Kuntana, Yasmi Purnamasari; Arrizqiyani, Tanendri; Safitri, Ratu (Sciences of Pharmacy, 2025)
Iron overload is linked to progressive impairment of organ function, with the liver being the primary site of deposition due to the lack of a physiological route for iron elimination. The maintenance of systemic iron balance depends on key regulatory proteins, including hepcidin (Hamp gene), ferritin light chain (Ftl gene), and transferrin receptor 1 (Tfr1 gene). This study tested the hypothesis that Deferiprone (DFP), an oral iron chelator, modulates the hepatic expression of Hamp, Ftl, and Tfr1 genes in an iron-overloaded rat model. Eighteen male Wistar rats (150-200 g) were randomly assigned into three groups: Normal (N), Negative Control (NC; induced with Iron Dextran), and Treatment (T; Iron Dextran + DFP). Iron overload was induced via intravenous injection of Iron Dextran (120 mg/kg BW) over 15 days at 3-day intervals, while DFP was administered orally (100 mg/kg BW) in three divided doses for 28 consecutive days. Gene expression was assessed using RT-PCR, and relative quantification was performed using the Livak method. The iron-overloaded rats showed marked upregulation of Hamp and Ftl and downregulation of Tfr1. Administration of DFP significantly reversed these alterations, decreasing Hamp and Ftl levels while restoring Tfr1 expression to levels comparable to normal controls. These results highlight the potential role of DFP in modulating hepatic iron-regulatory genes under iron overload conditions.